OPTIMASI PEMBUATAN PEREKAT KAYU ALAMI DENGAN MEMANFAATKAN LIMBAH PENYAMAKAN KULIT - Budhi Indrawijaya; Anggun Windarti; Elly Suryani (Jurnal Ilmiah Teknik Kimia, 2020)
In the leather tanning industry, split leather is the bottom that does not have a layer of      genuine leather. In one ton of garaman skin (fresh skin that has been preserved with salt) An estimated 11.5% split skin or the amount of 115 kg. There are still many that are produced later which are used for other purposes that can obtain added value of these products, for   example for making krecek (skin crackers). Research has been carried out to utilize the    split-lit waste from the leather tanning industry. Therefore this research of skin waste was carried out to produce glue using the collagen hydrolysis process using a hydrochloric acid catalyst (HCl). The process of hydrolysis in this experiment using HCl catalyst which run in beaker glass with magnetic stirrer. Then with a certain temperature-split skin is heateduntil it becomes thick and the solution filtered. After the filtrate is evaporated in the oven until a constant weight in the form of glue. From the experiments have been conducted on the variable the ratio between the weight of substances reacting to the volume of water, with 5% HCl catalyst as much as 10 mL, stirring speed of 250 rpm and temperature 70-75oC obtained under optimum conditions at the reaction time of 3 hours that is cow leather in the ratio of matter 30gr/200 mL water  of reagents with the results of glue as much as 6.90gr 10.8 grams, the yield is 35.35%, and adhesive firmness of 15.41kg/cm2. Whereas for goat leather in the ratio of matter 20gr/200mL water  with the results of glue as much as 6.90gr, the yield is 28.66%, and the adhesive firmness is 7.70kg/cm2